Ética do discurso e educação: do agir comunicativo à racionalidade discursiva - Knapp, Irene Monica (2007)
The dissertation to intend to broach pertinent points to the ethics and its relation with the education in the actual scene, focusing the problematic of the rationalization of the world. This phenomenon is legitimated for the technological potential of science and for the human attitudes implied in this process. The reduction of the rationality to the technician-instrumental aspects restricts the argument space about problematic questions concerning a common world that requires the agreement with the other. In the practical-moral field, the monological attitude restricted the ethical questions to an individualism way of life, limiting the reflexive potential of the subject about his act. And this reflexive potential is only possible of being carried through the practical discourse. The consequences of subjectivist ethics had reached global scale and argue the parcel of responsibility in the face of current problems, which demand the use of a communicative rationality in a rationally motivated effort. Habermas considers the reasons resource on behalf of communicative rationality, in perspective of that it is possible to rescue validity pretensions involving not only the subject world, but also the social and subject world present in the vital context. The method of the discourse, presented for the philosopher in his Ethics of the Discourse, asserts that the participants has to leave their self-centered position for the agreement with the other, assuming the responsibility about their utterances. In the education, the theoretical subsidies present in the Ethics of the Discourse to be able to contribute to act of the different rationalities for the benefit of the knowledge construction